SAD CULTURE: AN ANALYSIS OF THE US’ MENTAL HEALTH ISSUES AS EXPRESSED IN SOCIAL MEDIA - Al Fajri, Bagas; Windarti, Ani; Ahdiani, Ulaya; Atmantika, Zanuwar Hakim (Rubikon : Journal of Transnational American Studies, 2023)
The exponential growth of social media has resulted in the establishment of significant communities, trends, and phenomena. Amidst these phenomena is the sad culture, where social media users comfortably express their mental concerns. This study is conducted to have a profound conclusion on Sad Culture as a phenomenon, using social influence theory to determine its cause of emergence. In addition, the meaning of the terminologies is discussed using appraisal theory. This study implements qualitative and content analysis research design. It is implemented by gathering the data from @mytherapistsays Instagram page and performing an in-depth content analysis. Upon conducting the research, it is concluded that Sad Culture is a type of cyberculture. It is formed due to the rapid development of ICT–social media in particular–and the rising number of mental illnesses in the US. It started as a trend, then grew massive due to conformity, a term under social influence theory defined as an act where the majority influences others to perform what is believed to be the norm. In @mytherapistsays Instagram account, ten appraisal items are found, comprising 10% positive and 90% negative items.